The impact of earnings management on perceived quality of earnings: the moderating role of ESG - Rahayu Lestari; Dewi Refianingrum Muthmainnah (AJAR (Asian Journal of Accounting Research))
Purpose – This study aims to examine whether investors perceive earnings management as opportunistic behaviour that impair earnings quality or as an enhancer of earnings informativeness in the context of developing countries. This study also investigates whether the presence of higher ESG activities can obscure investors’ assessment of earnings management and thus affect investors’ response to managed earnings. Design/methodology/approach – Final sample is 166 firm-year observations from non-financial public companies in Indonesia with the observation period 2019–2023. This study uses two-step estimator of GMM with robust standard errors. Findings – We find that earnings management is viewed as an action that increases the informativeness value, thereby increasing investor reactions to earnings announcements. ESG was found to significantly affect investors’ valuation on managed earnings. Overall, investors still give a large reaction to managed earnings because of the high ESG performance considered by investors. This effect is more significant in the case of income decreasing earning management. Research limitations/implications – The study employs small sample and focuses in the Indonesian context. Future research could expand the sample or conduct international studies. Practical implications – This study provides an understanding that companies may manage earnings to increase informativeness value of earnings and utilize high ESG to hide their opportunistic actions. Regulators play an important role in preventing such opportunistic actions by increasing the monitoring of ESG activities and promote transparency in ESG reporting. Originality/value – This study extends existing literature by examining how ESG affect investor reaction to managed earnings.